ENHANCING CONSUMER ENGAGEMENT THROUGH CONTENT MARKETING - Makki, Ali (E-Journal VFU, 2024)
In today’s landscape, where content pervades every aspect of our lives and connectivity is ubiquitous, reaching the audience directly has become more attainable. However, this convenience comes at the cost of heightened efforts from businesses to captivate consumers. The digital realm has ushered in novel business prospects, with the amalgamation of various industries giving rise to a fresh market mindset centered around the platform economy. Adapting business strategies, particularly in the face of a pandemic, has evolved into a vital survival imperative, prompting companies to seek innovative solutions to navigate the challenges posed by new realities. The surging popularity of content marketing is no happenstance, as evidenced by numerous institutional studies delving into marketing trends. Creating and sharing content aligned with consumer interests and cultivating relationships through it presents an invaluable opportunity. Disregarding digitization processes is synonymous with being outdated. This article endeavors to spotlight the advantages of employing content marketing as a strategic tool for business success. At its core, the pursuit of a meaningful connection with the audience through compelling content lies at the heart of the gig economy, responding to evolving consumer habits and steering new market dynamics.